Nature as school: Indigenous Mentawai children’s play activities based on local wisdom for enriching motor skills - Komaini, Anton; Kiram, Yanuar; Erianjoni; Andika, Heru; Handayani, Sri Gusti (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
Childhood is a period of growth and motor development. Therefore, analyzing strategies to prevent motor delays is very important. One strategy to prevent motor delays is play activities. Therefore, this study aimed to obtain in-depth information about play activities based on local wisdom of indigenous Mentawai children while enriching children’s motor skills. The methodology of this study was qualitative research. The sample included six indigenous Mentawai children and three parents of participating children. This study employed data triangulation—specifically, semi-structured open interviews, observation, and document analysis—as methods of data collection. The results of the study conveyed that play activities based on local wisdom can enrich the motor skills of indigenous Mentawai children. Based on the results, the researcher advised parents not to limit children from doing outdoor activities and to provide opportunities for children to explore activities. Play activities based on the local wisdom of indigenous Mentawai children can enrich motor skills, so that it can minimize the occurrence of motor delays in early childhood.